ผลของโปรแกรมการบำบัดสัมพันธภาพระหว่างคู่สมรสแบบสั้นต่อพฤติกรรมการดื่มสุราในผู้ป่วยโรคติดสุรา - ธิษณามา โพธิ์งาม (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The objectives of this quasi-experimental pretest-posttest control group research design. were to compare 1) alcohol consumption behavior among patients with alcohol dependence before and after receiving a brief couple relationship therapy program, and 2) alcohol consumption behavior among patients with alcohol dependence who received brief couple relationship therapy program and those who received regular care. The sample were 40 family of patients with alcohol dependence and his spouse who had been following up after treatment at the Psychiatry and Neurology outpatient department of Phramongkutklao ( PMK ) Hospital. The patients were recruited from those who completed the PMK rehabilitation model within a year. The samples were matched- pair to have similar characteristics by patient’ alcohol consumption score and age, and then randomly assigned to either experimental or control group, 20 families in each group. The experimental group received the brief couple relationship therapy program developed from Fals-Stewart et al.(2005), whereas the control group received regular care. The research instruments are: 1) the brief couple relationship therapy program, 2) the demographic questionnaire, 3) the AUDIT scale ,4) the Alcohol Timeline Follow back, and 5) the Dyadic Adjustment Scale. All instruments were verified for content validity. The reliability of the 4th instrument is reported with Pearson product moment correlation as of .97. Descriptive statistics and t-test were used in Data analysis. The conclusions of this research are as follows: 1) after the experiment, the alcohol consumption behavior of patients with alcohol dependence who received brief couple relationship therapy program was significantly different than that before at p.05, by which the total number of drinks and the percentage of heavy drinking days were lower whereas the percentages of days abstinent were higher than that before; 2) after the experiment, the alcohol consumption behavior of patients with alcohol dependence who received brief couple relationship therapy program was significantly different from those who received regular care at p.05, by which the total number of drinks and the percentage of heavy drinking days among the experimental group were lower whereas the percentages of days abstinent were higher than those in the control group.